Protocol for durum wheat milling into semolina - CGIAR Research Program on Wheat (2020)
We are now currently and routinely using the durum wheat milling protocol for the production of semolina and most of the durum wheat samples that were analyzed in the laboratory of the CIMMYT headquarters, were milled into semolina rather than flour.